Archaeology a very short introduction - Bahn, Paul G. 1953- (Very short introductions, 2012)
This 'Very Short Introduction' provides an up-to-date account of the problems, concerns and nature of archaeology, with reference to all the latest archaeological techniques, theories, and excavations